Multicenter Analytical Validation of Aβ40 Immunoassays - van Waalwijk van Doorn, Linda J. C.; Kulic, Luka; Koel-Simmelink, Marleen J. A.; Kuiperij, H. Bea; Versleijen, Alexandra A. M.; Struyfs, Hanne; Twaalfhoven, Harry A. M.; Fourier, Anthony; Engelborghs, Sebastiaan; Perret-Liaudet, Armand; Lehmann, Sylvain; Verbeek, Marcel M.; et al. (Frontiers in Neurology, 2017)
Background: Before implementation in clinical practice, biomarker assays need to be thoroughly analytically validated. There is currently a strong interest in implementation of the ratio of amyloid-β peptide 1-42 and 1-40 (Aβ42/Aβ40) in clinical routine. Therefore, in this study, we compared the analytical performance of six assays detecting Aβ40 in cerebrospinal fluid (CSF) in six laboratories according to a recently standard operating procedure (SOP) developed for implementation of ELISA assays for clinical routine. Methods: Aβ40 assays of six vendors were validated in up to three centers per assay according to recently proposed international consensus validation protocols. The performance parameters included sensitivity, precision, dilutional linearity, recovery, and parallelism. Inter-laboratory variation was determined using a set of 20 CSF samples. In addition, test results were used to critically evaluate the SOPs that were used to validate the assays. Results: Most performance parameters of the different Aβ40 assays were similar between labs and within the pre-defined acceptance criteria. The only exceptions were the out-of-range results of recovery for the majority of experiments and of parallelism by three laboratories. Additionally, experiments to define the dilutional linearity and hook-effect were not executed correctly in part of the centers. The inter-laboratory variation showed acceptable low levels for all assays. Absolute concentrations measured by the assays varied by a factor up to 4.7 for the extremes. Conclusions: All validated Aβ40 assays appeared to be of good technical quality and performed generally well according to predefined criteria. A novel version of the validation SOP is developed based on these findings, to further facilitate implementation of novel immunoassays in clinical practice.